Sosialisasi Edukasi Penanganan Pasca Panen Kopi Untuk Kelompok Tani Kopi Alir Coffee - Iswara, Mochammad Agung Indra; Mufid; Anggerta, Lintang Alivia; Amrullah, Ustman Syah; Ro'isatin, Umi Anis; Setiawan, Ikhsan (PELITA NUSA TENGGARA, 2025)
Coffee is a favorite of the Indonesian people, especially with the increase in coffee business after the COVID-19 pandemic, so the demand for coffee raw materials from farmers has also increased. Residents of Ketindan village on the slopes of Mount Arjuna, under the guidance of Alir Coffee, take advantage of this condition by cultivating coffee, although the technology used is still simple, and post-harvest waste has not been managed properly. To improve production efficiency and waste management, the Department of Chemical Engineering – State Polytechnic of Malang held PpM activities, namely educating farmers through presentation methods and question and answer discussions, the activity ended by providing feedback to participants and handing over a set of Huller Coffee tools to increase the productivity of coffee farmers. Feedback data processing is done by the Likert scale method. The results of the PkM activity, show that residents are very enthusiastic in attending socialization activities and many participants in question and answer discussion sessions, while the Likert scale results obtained a percentage score of 95% which means that partners are very satisfied with this socialization activity. With the knowledge of post-harvest coffee management and processing, this activity is running smoothly and is expected to increase the knowledge of post-harvest coffee education, increase the economic potential for residents, and can be implemented sustainably.